VITAMIN D LEVELS OF OUTPATIENTS ADMITTED TO A UNIVERSITY HOSPITAL IN THE MARMARA REGION OF TURKEY OVER 3 YEARS - (:unkn) unknown (DE GRUYTER POLAND SP ZOO, 2019)
Background: Vitamin D regulates calcium and phosphorus metabolism, and it is essential for bone formation. Several factors can affect vitamin D levels in plasma. In present study we compare vitamin D levels of outpatients, who admit to Maltepe University Hospital between 2011 and 2013 and had vitamin D measurements regarding gender, age, and season. Methods: Hospital records were evaluated to identify the outpatients with vitamin D levels and their gender, age, and vitamin D levels and the seasons of measurements were recorded. Results: Data of 4860 subjects (74% female) were analyzed and 69.2% were between 18-64 years old. Vitamin D levels were as follows: 43.1% <= 10 ng/mL, 31.9% between 10 ng/mL and 20 ng/mL, 16.1% between 20 ng/mL and 30 ng/mL, and only 8.9% >= 30 ng/mL. The number of females with vitamin D levels < 10 ng/mL was significantly higher than that of males, while the number of males with vitamin D levels between 10 ng/mL and 20 ng/mL was significantly higher than that of females (P = 0.001) for each of the individuals, 6.2% and 11.1% had sufficient levels in winter and summer, respectively. Overall, it was observed that 6.6% of individuals between 18-44 years old, 8.2% of individuals between 45-64 years old and 10.3% of individuals over 65 years old had vitamin D levels > 30 ng/mL. Conclusions: The prevalence of vitamin D deficiency in outpatients of Maltepe University Hospital in Marmara region was 75% (< 20 ng/mL).
Keywords: vitamin D; season; gender; age; D DEFICIENCY; SEASONAL-VARIATIONS; POPULATION; DETERMINANTS; EXPOSURE; WOMEN; AGE